PUBLIC POLICY AND GOVERNMENT COMMUNICATION: ENHANCING COMMUNITY COMPLIANCE THROUGH TRUST AND POLITICAL AWARENESS IN CIANJUR - Rachmat Rachmat; Neli Yuliawati; Hidayat Hidayat (RADJA PUBLIKA, 2026)
The effectiveness of government administration largely depends on the level of public compliance. However, the situation in Cianjur Regency indicates a persistent gap between government policy design and its implementation by the community. This study aims to examine the effects of Public Policy Quality and Government Communication on Public Trust and Community Compliance, while also investigating the mediating role of Public Trust and the moderating role of Political Awareness. Using a quantitative approach with an explanatory survey method, data were collected from 310 respondents in Cianjur through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that both Government Communication and Public Policy Quality have positive and significant effects on Public Trust. However, in influencing Community Compliance, only Government Communication demonstrates a significant direct effect. In contrast, Public Policy Quality, the mediating effect of Public Trust, and the moderating effect of Political Awareness do not show significant influences on Community Compliance. These results suggest that effective government communication serves as the most dominant instrument and primary determinant in ensuring citizens’ compliance with local government policies. This study contributes to the academic literature on the determinants of community compliance by providing empirical evidence regarding the roles of policy quality, government communication, public trust, and political awareness. Furthermore, it offers an empirical model for local governments to enhance governance effectiveness through communication-based strategies aimed at improving the implementation and success of public development programs.